PERCORRENDO OS CAMINHOS DA RELAÇÃO ENTRE AS POLÍTICAS PÚBLICAS DE SAÚDE E DO MEIO AMBIENTE - Debora Aparecida da Silva Santos; Pedro Vieira de Azevedo; Jullianna Vitorio Vieira de Azevedo; Telma Lúcia Bezerra Alves; Amaury de Souza (Revista de Políticas Públicas, 2016)
This study presents an analysis of the path taken in the relation between public health policies and the environment in a broader context, through a literature review on the topic. The approach of environmental issues with the health promotion movement allows a broader understanding of the health-disease process. This proposal selects the integration across sectors as a condition for the establishment and implementation of public policies as a way to ensure better environmental conditions. In this way, a broad discussion of the importance of various social actors related to health and the environment is essential, understanding that an interdisciplinary action by recognizing the public policies improves people's quality of life and, consequently, contributes to a more balanced society ecologically.